Storm of the century the Labor Day hurricane of 1935 - Drye, Willie (National Geographic, 2003)
"On Labor Day Weekend, 1935, America took a body blow. Already reeling from the Great Depression, the battered nation was just starting to get back on its feet when nature delivered a knockout punch: the greatest hurricane ever recorded on our shores. This nameless, violent killer blasted buildings to smithereens with 200-mile-an-hour winds and a raging storm surge that overwhelmed everything in its path. The wonder is not that so many died in the Florida Keys, but that anyone survived at all." "Author Willie Drye deftly weaves an hour-by-hour, often moment-by-moment tapestry of first-person accounts of the fateful storm. He evokes the frugal life of the handful of families who inhabited these tiny, low-lying islands and explains why good intentions and political expediency sent hundreds of veterans to New Deal labor camps in one of the most remote places in America. He describes the storm gathering fury off Cuba, as it eludes the U.S. Weather Bureau's detection systems and finds the S.S. Dixie, a passenger liner, which unwittingly sets out from New Orleans on a collision course with the heart of the gale. As the storm warnings mount, government bureaucrats dither while the hurricane zeroes in on the Keys, striking its shocked and terrified victims with unimaginable force."